The Use Of Scaffolding Strategy On Students’ Reading Comprehensions At The Seventh Grade Of SMP N 12 Pematangsiantar - Sihombing, Cindy R.; Sitanggang, Anita; Sihombing, Partohap Saut Raja (Innovative: Journal Of Social Science Research, 2025)
This study aims to determine the effect of the scaffolding strategy on reading comprehension of procedural texts among seventh-grade students at SMP N 12 Pematangsiantar. The scaffolding strategy was used to provide gradual support to students in understanding more complex texts. This research employed a quasi-experimental design with two groups: the experimental group taught using the scaffolding strategy and the control group taught using conventional methods. Data were collected through pre-test and post-test assessments. The analysis showed a significant improvement in the experimental class's reading comprehension scores after the treatment. The average pre-test score for the experimental class was 41.8, which increased to 60.9 after the treatment. In contrast, the control class only showed a slight improvement, from 43.1 to 48.5. The t-test result was 11.929, which is higher than the t-table value of 1.670, indicating that the alternative hypothesis was accepted and the null hypothesis was rejected. This study concludes that the scaffolding strategy is effective in improving students' reading comprehension, especially in procedural texts.